MEDICINAL BENEFITS OF NIGELLA SATIVA (BLACK CUMMIN) SEED EXTRACT: A REVIEW - Shiitu, Bello Sirajo; Othman, Fauziah; Abdullah, Faez Firdaus Jesse; Basr, Hamidon; AD, Zagga; Aliu, Abdulhameed; Eshak, Zolkapli (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
There is now growing attention in the use of natural product in the treatment of many diseasesboth acquired and congenital. Nigella Sativa L. (N. sativa) is a family member of theRanunculaceae. It is an erect plant that is grown annually in the Mediterranean countries andsome North African countries. It is also cultivated in countries like Malaysia, Iran, India andChina. N. sativa has been in use as traditional medicinal plant for thousands of years. It wasused as remedy for several diseases over two thousand years ago. But recently researchers haveshown that extract of the seeds of N sativa and its oil are of pharmacological benefits, such asanalgesic and anti-inflammatory activities, it is also beneficial as antihypertensive,hypoglycaemic, antihistamine, antibacterial, antifungal, anthelminthic and also anti-tumourremedy. In conclusion this review indicates that the benefit of Nigella sativa (black cumin)seed extract can be used as a neuro-protective agent in both human and animal.